Design of Lightweight Cryptographic Model for End-to-End Encryption in IoT Domain - Chatterjee, Runa; Chakraborty, Rajdeep; Mondal, J.K. (IRO Journal on Sustainable Wireless Systems, 2019)
Digitalization rapidly connected the entire world. Everyday an enormous volumes of digital data produced by billions of intelligent devices which requires safe transmission over internet. If we look into embedded environment, handling massive volume of data is impractical for low power and low memory devices which leads to lightweight concept. The proposed lightweight model includes many symmetric key sequentially. The model follows fiestel network structure where 64 bits input block divided by two 32 bits blocks. Then every half undergoes through various symmetric key algorithms like TE (Triangular Encryption), RPPT (Recursive Pared Parity Technique), RPSPNC( Recursive Positional Substitution on Prime-Nonprime of Cluster), TB(Transformation of Bits) and bits rotation process. A triangular bit sequence generated by TE and from there various encryption as well as decryption techniques[1] have generated by reading bits in a certain order. RPPT encrypts bits by executing logical OR of successive bits. Bit swapping technique is used by TB for encryption and decryption. RPSPNC interchanges bits on the basis of prime-non prime bit position and considers any in between bit sequence as a cipher text. Lastly two resultant sub-blocks are merged to produce cipher text of 64 bits. To check the acceptance of the proposed model, comparisons take place with popular symmetric key algorithm AES and one embedded algorithm RPPT+TB. Software parameters like entropy, n-gram(4-gram), non-homogeneity, histogram are analysed. Hardware analysis of the model ensures us that it falls into lightweight domain by comparing the GE (Gate equivalent) with the ISO /IEC standard value ranges between 1000-2000GE.
Keywords: Cryptosystem; CBC; End-to-End encryption; lightweight; IoT